2017
DOI: 10.31055/1851.2372.v52.n2.17434
|View full text |Cite
|
Sign up to set email alerts
|

Bryophytes as a material to build birds’ nests in Brazil.

Abstract: Resumen: Briofitos como material para la construcción de los nidos de pájaros en Brasil. Los nidos de aves son construcciones complejas, hechas para proporcionar un ambiente protegido y seguro para que los huevos y las crías de pájaros se desarrollen. Las ramas y hojas representan materiales comunes de anidación, transportados por las aves en sus picos. En algunas oportunidades los materiales transportados son mayores que las propias aves. Además de las ramas y hojas, las aves también usan otros materiales (au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Supporting our results, Calvelo et al [4] have shown that mosses and liverwort are the dominant components in nest construction. However, De Almeida et al [10] report a higher number, with 57 species of bryophytes in 21 birds' nests, but the bird's nest does not contain any information regarding the specific species of bird responsible for constructing it. Thus, the researchers point out that liverworts present a higher number of species; however, mosses are the structural elements of nest building.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting our results, Calvelo et al [4] have shown that mosses and liverwort are the dominant components in nest construction. However, De Almeida et al [10] report a higher number, with 57 species of bryophytes in 21 birds' nests, but the bird's nest does not contain any information regarding the specific species of bird responsible for constructing it. Thus, the researchers point out that liverworts present a higher number of species; however, mosses are the structural elements of nest building.…”
Section: Resultsmentioning
confidence: 99%
“…Bryophytes increase water retention, thermal insulation, and antimicrobial activity [3,8,9]. There are many studies on nests constructed with vascular plants, but few on nests constructed with bryophytes [7,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because some birds and bryophytes share the same habitats, these birds may serve as animal vectors that allow these small plants to reach areas that they would not reach otherwise, or help reach them quicker. The behavior of birds can aid in directed and long-distance movement of bryophytes as they may act as dispersers in local sites through foraging and nesting (Calvelo et al, 2006;Parnikoza et al, 2012;Amélio et al, 2017;Parnikoza et al, 2018), and transcontinentally through migratory movements (Chmielewski & Eppley, 2019). Birds can disperse bryophytes long distances via ectozoochory, by external transportation (Lewis et al, 2014), and may be able to do this via endozoochory, through internal ingestion, as has also been shown with ferns and other herbs (Lovas-Kiss et al, 2018;Blanco et al, 2019;Hervías-Parejo et al, 2019;Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
“…However, because some birds and bryophytes share the same habitats, these birds may serve as animal vectors that allow these small plants to reach areas that they would not reach otherwise, or help reach them quicker and more frequently. The behavior of birds can aid in directed and longdistance movement of bryophytes as they may act as dispersers in local sites through foraging and nesting (Amélio et al, 2017;Calvelo et al, 2006;Parnikoza et al, 2012Parnikoza et al, , 2018, and transcontinentally through migratory movements (Chmielewski & Eppley, 2019). There has been evidence of migratory birds carrying bryophytes via ectozoochory, by external transportation (Lewis et al, 2014).…”
mentioning
confidence: 99%